Morphology development of ZnO produced by sonothermal process - Siriprapha Jattukul (2018)
Wurtzite ZnO (hcp) was produced by the 80 °C sonothermal reactions of 1:5, 1:10, and 1:20 molar ratios of Zn(NO3)2· 6H2O:NaOH in water, containing 2 g, 5 g, 10 g, and 20 g of polyethylene glycol (PEG) with the molecular weights (MWs) of 6000, 10000, and 20000 for 1 h, 3 h, and 5 h. ZnO phase with different morphologies was detected. When the amount of NaOH, both MW and the amount of PEG, and the experimental time were increased, the products still retain their single phase, but their morphologies were changed from nanoplates in clusters to nanospears with sharp tips gathering together in the shape of flowers, and long nanorods with oval tips in clusters. In the present work, formation mechanism of these products was also discussed. © 2011 Elsevier Ltd and Techna Group S.r.l.